Book Review: Bobrova NF, editor. A monograph of Retinoblastoma - G.D. Zhaboedov (Ukrainian Society of Ophthalmologists, 2020)
A monograph of the current aspects of diagnosis and management of retinoblastoma (RB), a pediatric ocular malignancy, was presented by an international team of authors from the Institute of Eye Diseases and Tissue Therapy, AMS of Ukraine, Odesa; Spizhenko Clinic Oncology Center, Kyiv, Ukraine; Jules Gonin Eye Hospital, Lausanne, Switzerland; and Retinoblastoma Referral Center, University of Siena, Italy. The book describes the current imaging modalities in the diagnosis of eye cancer, such as ultrasonography, spectral optical coherence tomography (SOCT), fluorescent angiography (FA) and magnetic resonance imaging (MRI). Details (procedural features, complications and outcomes) with regard to first-line eye-saving treatment, polychemotherapy (systemic, intracameral, intravitreal, intra-arterial, and combination chemotherapy) and second-line eye-saving treatment, radiation therapy, for retinoblastoma are discussed. Specifically, the following is described: a RB presenting a high risk of dissemination; novel enucleation techniques involving use of high frequency electric welding of biological tissues to prevent intraoperative dissemination of tumor cells; and prevention and management of anophthalmic syndrome. The monograph presents the features of RB regression, and development and treatment of tumor recurrence. It also includes the latest data on retinoblastoma diagnosis and treatment under COVID-19 pandemic conditions. The book is illustrated with 322 color photographs and 21 tables, and includes 27 example cases. It was written for ophthalmologists, oncologists, eye surgeons, family physicians and pediatricians